Doing the right things right, all the time - Lovett, J. Robert
J. Robert Lovett explains how Air Products and Chemicals has brought about a tenfold reduction in the time it takes to define a new product.
The quality process can be applied as effectively to R&D as to any other function in a business, Air Products and Chemicals has learned.
Everyone wants to do the right things right, all the time. The quality approach increases one's chances of achieving this goal. To do the right thing, research must be planned with a full understanding of the customer's expectations. This only happens by fostering a relationship of trust and understanding that enables frequent, open communication between the right people. The payoffs in reducing product development time are enormous. Doing the right things right is also critical. By using classic quality tools such as Pareto charts and problem solving to remove nonconformances, and statistical quality control to monitor raw material variability, Air Products and Chemicals, Inc. was able to reduce the time to define commercial process conditions for a new product tenfold. Most problems in R&D are caused by lack of understanding of customer requirements and inadequate planning in executing the work, not by a lack of technical excellence or poor science.